Konseling Eye Movement Desensitization and Reprocessing (EMDR) dalam Penanganan Traumatik - Tharifah Haibaty Kurniawan; Muhammad Yunus Efendi; Marissa Nabilla Putri Anwar; Bakhrudin All Habsy (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
Eye Movement Desensitization and Reprocessing (EMDR) counseling is a counseling method that involves rapid and repetitive eye movements to bring up negative events, and replace them with more positive feelings. EMDR was developed by Shapiro in 1987 and became known in 1989. EMDR counseling focuses on handling traumatic problems. The method used in this research is a qualitative method with the type of literature study, which is to collect data and sources related to the research topic being studied. The data that has been collected is then analyzed using the description analysis method. This research is expected to help add new insights in depth related to Eye Movement Desensitization and Reprocessing (EMDR) counseling. The results of this study include, namely (1) basic concepts of EMDR counseling, (2) purpose of EMDR counseling (3) the stages in EMDR counseling, and (4) the advantages and disadvantages of EMDR counseling.